2019
DOI: 10.3390/jcm8020271
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Improves Functional Recovery via Regulation of the RAGE/JNK/NF-κB Signaling Pathway after Brain Injury

Abstract: Brain injuries are a serious global health issue and are the leading cause of neurodegeneration. To date, there is no proper cure and treatment for brain-injury-induced neuropathological conditions because of a lack of sufficient knowledge and the failure to develop a drug due to the multi-pathological conditions in the brain. Herein, we explored the neurotherapeutic effects of Nicotinamide (NAM), against brain injury-induced neurodegeneration and behavioral problems. Treating injured mouse brains with NAM, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…RAGE-related pathway activation may promote the overexpression of inflammatory factors and peroxides through JNK/NF-κB signaling, which participates in organ damage. In this process, the phosphorylation of JNK protein is a key link in signal pathway activation [24][25][26]. In the present study, we found that expression of RAGE, JNK, p-JNK, NF-κB, and p-NF-κB was increased in STZ-induced diabetic rats, suggesting that RAGE activation can activate JNK/NF-κB signaling through the phosphorylation pathway to participate in the apoptotic destruction of pancreatic tissue.…”
Section: Discussionsupporting
confidence: 57%
“…RAGE-related pathway activation may promote the overexpression of inflammatory factors and peroxides through JNK/NF-κB signaling, which participates in organ damage. In this process, the phosphorylation of JNK protein is a key link in signal pathway activation [24][25][26]. In the present study, we found that expression of RAGE, JNK, p-JNK, NF-κB, and p-NF-κB was increased in STZ-induced diabetic rats, suggesting that RAGE activation can activate JNK/NF-κB signaling through the phosphorylation pathway to participate in the apoptotic destruction of pancreatic tissue.…”
Section: Discussionsupporting
confidence: 57%
“…p-CREB, the target protein of p-AMPK and a regulator of neuroinflammation [50], was also significantly downregulated in the cortex and hippocampus of the rmTBI mouse brain. Activation of NF-κB has been cited in brain injuries [51]. It was interesting to observe that the treatment with melatonin reversed the energy depletion via regulating the AMPK level, as well as the pro-survival CREB proteins, in the rmTBI plus Mel-treated group, reflecting neuronal injury (Figure 1C).…”
Section: Resultsmentioning
confidence: 86%
“…For morphological examinations, we conducted Nissl’s staining, which indicates the number of neuronal cells loss. Briefly, as previously described [33,34], the brain slides were washed with 1% PBS (0.01 M) followed by staining with a solution of Cresyl violet (0.5%) comprising a few drops of glacial acetic acids for 8–10 min. After that, sections were washed with distilled water followed by dehydration in graded ethanol of 70%, 95%, and 100%.…”
Section: Methodsmentioning
confidence: 99%